Distinct Revocable Data Hiding In Ciphered Image - Patil, Anamika; Bafna, Pooja; Pounikar, Mona; Badgujar, Pranjal (International Journal of Computer Sciences and Engineering, 2014)
The rapid development of data transmission through internet made it easy to send the data at faster rate to the destination. This work proposes a scheme for distinct revocable data hiding in ciphered images. At first, a content owner encrypts the original image with help of the encryption key. Then, the LSB of the encrypted image are compressed using a data-hiding key by the data hider to create a space to include some data. If a receiver has the data-hiding key, the additional data can be retrieved easily. And if the receiver has the encryption key, he can easily decrypt the received data to get the image similar to the original one, but cannot obtain the data. In case if the receiver has both the data-hiding key as well as the encryption key, he can obtain the data and regain the original image content. Hence, in order to transfer the data securely to the destination without any modifications, there are many techniques like cryptography and about the various steganographic algorithms like Least Significant Bit (LSB) algorithm.